Development of Stem-Based Mathematics Learning Modules with The PBL Model to Improve Mathematical Communication Ability - Sri Rahayu Ningsih; Ella Andhany (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
The research aims to develop a learning module that employs a STEM–integrated PBL framework to strengthen the mathematical communication proficiencies of secondary school learners. Its attributes encompass being sound, functional, and productive. The methodology adopted in this study is the R&D approach, utilising the ADDIE framework for development, which encompasses analysis, design, development, implementation, and evaluation. The subject pool for this research comprised the entirety of the 30 students enrolled in class VII at Muhmmadiyah 7 Medan Junior High School. The study’s findings indicated that the learning module’s validity assessment placed it within the highly valid spectrum, with an average score of 87,41%. Furthermore, the assessment of the learning module’s practicality, derived from teacher questionnaires, placed it in the highly practical category with a 95% rating, while student questionnaires yielded an 86,14% rating, also denoting a highly practical standing. Additionally, the post-test outcomes revealed an enhancement in students’ mathematical communication prowess, marked by a 77,58% surge, thus categorising it as effective. Hence, the learning module, integrating the STEM-based PBL model to elevate Junior High School Students’ Mathematical Communication Skills, demonstrates both practicality and effectiveness.